Kinetic Isotope Effect in the Hydrogenation and Deuteration of Graphene. (2nd November 2012) - Paris, Alessio; Verbitskiy, Nikolay; Nefedov, Alexei; Wang, Ying; Fedorov, Alexander; Haberer, Danny; Oehzelt, Martin; Petaccia, Luca; Usachov, Dmitry; Vyalikh, Denis; Sachdev, Hermann; Wöll, Christoph; et al.
Abstract Time‐dependent photoemission spectroscopy is employed to study the kinetics of the hydro‐genation/deuteration reaction of graphene. Resulting in an unusual kinetic isotope effect, the graphene deuteration reaction proceeds faster than hydrogenation and leads to substantially higher maximum coverages of deuterium (D/C≈35% vs H/C≈25%). These results can be explained by the fact that in the atomic state H and D have a lower energy barrier to overcome in order to react with graphene, while in the molecular form the bond between two atoms must be broken before the capture on the graphene layer. More importantly, D has a higher desorption barrier than H due to quantum mechanical zero‐point energy effects related to the C–D or C–H stretch vibration. Molecular dynamics simulations based on a quantum mechanical electronic potential can reproduce the experimental trends and reveal the contribution of the constituent chemisorption, reflection, and associative desorption processes of H or D atoms onto graphene. Regarding the electronic structure changes, a tunable electron energy gap can be induced by both deuteration and hydrogenation.